The influence of impurities on the crystal structure and mechanical properties of additive manufactured U–14 at.% Nb. (15th March 2017) - Wu, Amanda S.; Brown, Donald W.; Clausen, Bjørn; Elmer, John W.
Abstract: Uranium-niobium alloys can exist with significantly different microstructures and mechanical properties, heavily influenced by thermomechanical processing history and impurities. Here, the influence of Ti and other impurities is studied on uranium-14 at.% niobium additively manufactured using laser powder bed fusion. Two different metallic impurity levels were investigated and a Nb equivalent (Nbeq ) composition is defined to represent the impurities. In-situ neutron diffraction during compression loading shows that increased Nbeq promotes the formation of γ°-tetragonal phase at the expense of α″-monoclinic phase, resulting in 2 × higher yield strength than water quenched α″ and a strain induced transformation to α″ with superelastic strains to 4.5%. Graphical abstract: